Spring 1994 Iowa report, Peter Petersen - Petersen, Peter C.et al (1994)
An annotated list of birds sighted by Peter Petersen and others. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of Spring 1994. Plustek - flatbed